To solve the quadratic equation \( x^2 + x + 0.25 = 0 \) using the perfect square trinomial pattern, we can first rewrite the equation.
Notice that \( 0.25 \) is \( \left( \frac{1}{2} \right)^2 \). We can rewrite the equation:
\[ x^2 + x + \left( \frac{1}{2} \right)^2 = 0 \]
Now, we can express the left side as a perfect square:
\[ \left( x + \frac{1}{2} \right)^2 = 0 \]
To solve for \( x \), we take the square root of both sides:
\[ x + \frac{1}{2} = 0 \]
Now, solving for \( x \):
\[ x = -\frac{1}{2} \]
Thus, the solution to the equation \( x^2 + x + 0.25 = 0 \) is:
\[ x = -0.5 \]
So, the correct response is:
x = -0.5 (or "x equals negative 0.5").